Endoscopic Retrograde Cholangiopancreatography in Nonagenarian Patients: Is It Really Safe? - Zain A Sobani; Daria Yunina; Anna Abbasi; Kevin Tin; Daniel Simkin; Mary Rojas; Yuriy Tsirlin; Ira Mayer; Rabin Rahmani (Korean Society of Gastrointestinal Endoscopy, 2018)
Background/Aims Literature on the safety of endoscopic retrograde cholangiopancreatography (ERCP) in elderly patients is divided. Based on this we decided to examine the safety of ERCP in nonagenarian patients. Methods A total of 1,389 patients, with a mean age of 63.94±19.62 years, underwent ERCP during the study period. There were 74 patients aged 90 years or older with a mean age of 92.07±1.8. Logistic regression showed that nonagenarian patients had a significantly increased odds of in-patient mortality (adjusted odds ratio [AOR]=9.6; 95% confidence interval [CI]=4, 23; p≤0.001). Charlson Comorbidity Index (CCI) ≥2 was also an independent predictor of in-patient mortality (AOR=2.4; 95% CI=1.2, 5.2; p=0.021). Age ≥90 was not associated with increased adverse events; however emergency procedures (AOR=2.4; 95% CI=1.5, 4; p<0.001) and CCI ≥2 (AOR=2.6; 95% CI=1.7, 4.0; p<0.001) were more likely to have adverse events. Conclusions Age ≥90 and CCI ≥2 are independently associated with increased odds of in-patient mortality in patients undergoing ERCP, whereas emergency procedures and CCI ≥2 are associated with an increased adverse event rate. Caution must be exercised when considering ERCP in patients aged ≥90 years and those with a CCI ≥2.